Denial of genocides in the twenty-first century - Der Matossian, Bedross, 1978- (University of Nebraska Press, 2023)
"Denial of Genocides in the Twenty-First Century discusses genocide denial in the twenty-first century by concentrating on communication, social networks, and public spheres of daily life"--